2019
DOI: 10.1128/jvi.01655-18
|View full text |Cite
|
Sign up to set email alerts
|

Structural Adaptations of Norovirus GII.17/13/21 Lineage through Two Distinct Evolutionary Paths

Abstract: Human noroviruses (huNoVs), which cause epidemic acute gastroenteritis, recognize histo-blood group antigens (HBGAs) as host attachment factors affecting host susceptibility. HuNoVs are genetically diverse, containing at least 31 genotypes in the two major genogroups (genogroup I [GI] and GII). Three GII genotypes, GII genotype 17 (GII.17), GII.13, and GII.21, form a unique genetic lineage, in which the GII.17 genotype retains the conventional GII HBGA binding site (HBS), while the GII.13/21 genotypes acquire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 56 publications
4
26
0
Order By: Relevance
“…The glycan binding profiles of huNoVs have been shown to be associated with their infection risk (3, 2429), and possibly also their prevalence (19, 21). We showed that the GII.13/21 huNoVs with the new GBS recognize a broad spectrum of terminal β-Gal-containing glycans, including mucin core 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glycan binding profiles of huNoVs have been shown to be associated with their infection risk (3, 2429), and possibly also their prevalence (19, 21). We showed that the GII.13/21 huNoVs with the new GBS recognize a broad spectrum of terminal β-Gal-containing glycans, including mucin core 2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a new variant of the previously rare genotype GII.17 became the predominant strain to cause outbreaks during the epidemic season of 2014–2015 (17, 18). Along with the antigenic change (17), the new GII.17 variant had a broader HBGA binding spectrum due to minor mutations at the conserved GII glycan binding site (GBS) (1821). Therefore, identification of the new huNoV-glycan interactions, especially those of the rare genotypes, is necessary to help in the prevention and control of huNoV-associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Structural analyses described the interactions between the virus capsid protein protruding domain (P-domain) and various HBGA oligosaccharides. Several distinct binding sites and modes of binding across the norovirus strains diversity have thus been uncovered, illustrating the adaptation of noroviruses to the human gut glycan diversity (Bu et al 2008;Cao et al 2007;Chen et al 2011;Choi et al 2008;Hansman et al 2011;Koromyslova et al 2015;Kubota et al 2012;Qian et al 2018;Shanker et al 2014;Singh et al 2015a).…”
Section: Hbga-binding Specificity Of Novs and Rvas Is A Driver Of Thementioning
confidence: 99%
“…An impact of the ABO phenotypes has also been reported, again with disparities across studies, likely explained by variations in the strains patterns of glycan recognition (Ruvöen-Clouet et al 2013). variants, which could contribute to their strong epidemiological impact (Chan et al 2015;Qian et al 2018;Zhang et al 2015). Unlike GII.4 strains, these emergent GII.17 strains failed to become dominant outside Asian countries where the major FUT2 mutant alleles confer a weak, albeit not null, secretor phenotype that potentially expands the susceptible fraction of the population (Ferrer-Admetlla et al 2009;Pang et al 2001).…”
Section: Hbga-binding Specificity Of Novs and Rvas Is A Driver Of Thementioning
confidence: 99%
“…Outbreak surveillance mostly identifies the genotypes that may already be efficiently transmitted in the population, and it is difficult to detect those variants before they are established in the local population. In particular, NoV genotypes such as GII.4 and GII.17 can have sudden transitions in their antigenicity or infectivity through a few amino acid mutations in their structural proteins (28)(29)(30). Before the transitions, the variants may have limited infectivity and circulate in the population at a relatively low level.…”
Section: Discussionmentioning
confidence: 99%